(untitled) (Journal of Philosophy Culture and Political Science, 2021)
The values of Kazakhstan’s independence are inextricably linked with the name of the First President N.A. Nazarbayev. It is he who plays the main and leading role in the creation of our modern Kazakhstan, in defining a clear Kazakhstani path of development. Kazakhstan became a member of the UN, OSCE, SCO and other international institutions, became a subject of international law. This allowed us to worthily occupy our niche in the world community and pursue an active foreign policy. Keу words: Unity of the people, independence of the country, international initiatives of Kazakhstan.